CASE REPORT: ANCYLOSTOMIOSIS IN PERSIAN MIX LOCAL CAT - Nugraha, I Wayan Syartama Hadi; Putriningsih, Putu Ayu Sisyawati; Batan, I Wayan (Buletin Veteriner Udayana, 2022)
Ancylostoma sp. is a common parasite that infects cats and is a major cause of ankylostomyosis. Ancylostoma sp . enter the nematoda class. Cats can be infected through foods containing eggs or infective larvae. A persian mix local cat named Roger, about 7 years old, weighs 3.5 kg, has diarrhea 3 to 4 times a day with blackish brown feces. Based on the results of a physical examination, the cat has diarrhea with a reddish anal mucosa, swelling in the mandibulary lymphogland dexter, eye mucosa, pale nose and mouth and dehydrated cats. The laboratory tests carried out were faecal examination with floating method, McMaster and routine hematology. Roger's cat was diagnosed with mild degrees of ancylostomiosis. Therapy given is pyrantel pamoat with a recommended dose of 6 to 25 mg/kg and the dose given is 20 mg/kg (0.5 tab). Kaolin pectin with recommended doses of 1 to 2 mL/kg (4.5 mL/day). Hematodine with a recommended dose of 0.5 to 2 mL/kg (injected 0.05 mL) intramuscular. Livron Bplex 1 tablet orally once a day for 10 days. Evaluation of cat cases 3 weeks post therapy found that cat cases had no diarrhea, mucosa of the mouth, eyes, ears, vagina, pink sphincter, Capillary Refil Time (CRT) of less than 2 seconds and good skin turgor. Stool examination results with negative native methods were not found for worm egg infestations.